Disease severity in patients with visceral leishmaniasis is not altered by co-infection with intestinal parasites. - Fitsumbrhan Tajebe; Mulusew Getahun; Emebet Adem; Asrat Hailu; Mulualem Lemma; Helina Fikre; John Raynes; Aschalew Tamiru; Zemenay Mulugeta; Ermias Diro; Frederic Toulza; Ziv Shkedy; et al. (Public Library of Science (PLoS), 2017)
Visceral leishmaniasis (VL) is a neglected tropical disease that affects the poorest communities and can cause substantial morbidity and mortality. Visceral leishmaniasis is characterized by the presence of Leishmania parasites in the spleen, liver and bone marrow, hepatosplenomegaly, pancytopenia, prolonged fever, systemic inflammation and low body mass index (BMI). The factors impacting on the severity of VL are poorly characterized. Here we performed a cross-sectional study to assess whether co-infection of VL patients with intestinal parasites influences disease severity, assessed with clinical and haematological data, inflammation, cytokine profiles and BMI. Data from VL patients was similar to VL patients co-infected with intestinal parasites, suggesting that co-infection of VL patients with intestinal parasites does not alter disease severity.